HEPARIN AND HYPOTAURINE SUPPLEMENTATION IMPROVE THE FERTILIZATION RATE OF SHEEP OOCYTES MATURED IN MEDIA CONTAINING L-CARNITINE IN VITRO - Rahmatullah, Rahmatullah; Setiadi, Mohamad Agus; Supriatna, Iman (Jurnal Kedokteran Hewan, 2022)
This study to do examine the effectiveness of using heparin and hypotaurine to improve the in vitro fertilization rate. In first stage, oocytes were matured in the maturation medium supplemented with 0.3 mg/mL L-carnitine to improve nuclear maturation. In second stage, matured oocytes were fertilized with semen incubated in fertilization medium supplemented with 0.1 IU/mL heparin and 10 M hypotaurine. The final concentration of sperm used was 5x106 spermatozoa/mL, and its interaction with oocytes was carried out for 12 hours in 5% CO2 incubator at 38.5 C. The results showed that percentage of oocytes that reached metaphase II was significantly higher (P0.05) in media supplemented with 0.3 mg/mL L-carnitine compared to control (88.24.9% vs 79.85.1%). Furthermore, fertilization rate was characterized by formation of 2 PN was significantly higher (P0.05) in media supplemented with heparin and hypotaurine than control (82.62.0% vs 73.32.4%). In conclusion, L-carnitine supplementation at dose of 0.3 mg/mL on maturation media was effective in increasing percentage of matured oocytes. The combination of 0.1 IU/mL heparin and 10 M hypotaurine in fertilization medium was also successful in elevating the percentage of fertilized oocytes.